2016
DOI: 10.5423/ppj.oa.08.2015.0159
|View full text |Cite
|
Sign up to set email alerts
|

3-Methylthiopropionic Acid of Rhizoctonia solani AG-3 and Its Role in the Pathogenicity of the Fungus

Abstract: Studies were conducted to determine the role of 3-methylthioproprionic acid (MTPA) in the pathogenicity of potato stem canker, Rhizoctonia solani, and the concentrations required to inhibit growth of R. solani under laboratory and plant house-based conditions. The experiments were laid out in a completely randomized design with five treatments and five replications. The treatments were 0, 1, 2, 4, and 8 mM concentrations of MTPA. The purified toxin exhibited maximal activity at pH 2.5 and 30°C. MTPA at 1, 2, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The metabolite MTPA in AG-3 plays a phytotoxic role during sheath blight because of its effect on membrane integrity in host cells 48 . Possible enzyme-encoding genes for the biosynthetic pathway of MTPA were observed in the transcriptome contigs.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolite MTPA in AG-3 plays a phytotoxic role during sheath blight because of its effect on membrane integrity in host cells 48 . Possible enzyme-encoding genes for the biosynthetic pathway of MTPA were observed in the transcriptome contigs.…”
Section: Resultsmentioning
confidence: 99%
“…The proficiency of S. sclerotiorum to acidify host tissue has long been known; an early study demonstrated a reduction in the pH of sunflower stems to as low as four during S. sclerotiorum infection ( Marciano et al, 1983 ). Other broad host range pathogens are capable of acidifying host tissue via production of various organic acids including phenylacetic acid (PAA) and 3-methylthioproprionic acid (MTPA), produced by R. solani , and tenuazonic acid, produced by A. alternata ( Meronuck et al, 1972 ; Bartz et al, 2012 ; Kankam et al, 2016 ).…”
Section: Fine-tuning Of Host Ph Is Widespread Among Broad Host-range mentioning
confidence: 99%
“…As well as the aforementioned effects on fungal virulence, some acids secreted by fungal pathogens exhibit direct phytotoxicity, a function that benefits fungi with a necrotrophic lifestyle. For example, botcinic acid, MTPA, OA, and tenuazonic acid produced by B. cinerea , R. solani , S. sclerotiorum , and A. alternata respectively, all have phytotoxic activity ( Visconti et al, 1987 ; Cutler et al, 1996 ; Kim et al, 2008 ; Kankam et al, 2016 ).…”
Section: Fine-tuning Of Host Ph Is Widespread Among Broad Host-range mentioning
confidence: 99%
“…Rhizoctonia solani produces toxin (RS toxin). The toxin is a host-selective pathogenicity determinant, meaning it only induces characteristic symptoms of corresponding hosts [22,23]. We anticipated that RS toxin could correlate with inoculum for resistance evaluation, as shown in rice pathosystem, where toxin of R. solani is a signi cantly correlated with phototoxic sensitivity and disease susceptibility [24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The latter can be used for primary screening on large collection of potato germplasms before eld evaluation, which would greatly reduce the amount of work load and time consuming, therefore improve the e ciency of resistance screen.Rhizoctonia solani produces toxin (RS toxin). The toxin is a host-selective pathogenicity determinant, meaning it only induces characteristic symptoms of corresponding hosts [22,23]. We anticipated that RS toxin could correlate with inoculum for resistance evaluation, as shown in rice pathosystem, where toxin of R. solani is a signi cantly correlated with phototoxic sensitivity and disease susceptibility [24][25].…”
mentioning
confidence: 99%